THE AUTHORITY OF THE CURATOR IN GENERAL SEIZURE OVER UNPAID PRELIMINARY SALE AND PURCHASE AGREEMENT (PPJB) OBJECTS IN LIMITED LIABILITY COMPANY BANKRUPTCY (A STUDY OF COMMERCIAL COURT DECISION NO. 29/PDT.SUS-GLL/2022/PN.NIAGA.JKT.PST) - Artanti Silitonga; Sunarmi Sunarmi; Robert Robert (Journal Analytica Islamica, 2026)
This study examines the authority of curators in enforcing general seizure (sita umum) over objects of Sale and Purchase Binding Agreements (Perjanjian Pengikatan Jual Beli/PPJB) that have not been fully paid in the bankruptcy of a Limited Liability Company, based on the Commercial Court Decision No. 29/Pdt.Sus-GLL/2022/PN.Niaga.Jkt.Pst. The main issue addressed is whether unpaid PPJB objects may be included in the bankruptcy estate (boedel pailit) and the extent of the curator's authority in managing and settling such objects. This research employs a normative juridical method using statutory and case approaches by analyzing Law Number 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations, along with relevant court decisions. The findings indicate that unpaid PPJB objects are, in principle, part of the bankruptcy estate since ownership rights have not been fully transferred, thereby granting the curator authority to impose general seizure and conduct management and settlement actions. Nevertheless, the exercise of such authority must consider the principles of justice and legal protection for good-faith buyers. The court's decision clarifies the legal standing of PPJB in bankruptcy proceedings and delineates the scope of the curator's authority.